БОЛЬ В СПИНЕ - В. И. Шмырёв; А. А. Фирсов (Архивъ внутренней медицины, 2014)
The problem of back pain is a pressing problem for many decades. The paper deals with the examination and treatment of back pain, particularly in the use of conservative treatment of pain, along with nonsteroidal anti-inflammatory drugs neurotropic Milgamma complexes.